KINERJA DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN KUTAI KARTANEGARA PERIODE 2009 – 2014 - Musriadi Musriadi (MAHAKAM: Jurnal Ilmu-Ilmu Sosial, 2013)
The purpose of this research objective of this study is to investigate and describe the performance of Parliament Kutai Regency Period 2009-2014 and the factors that affect the performance of Kutai district legislature in the era of regional autonomy. The data used in this study are primary and secondary data. Primary data compiled from the observations and interviews with legislators Kutai regency period 2009 - 2014 and the parties associated with the implementation of duties and functions as Parliament Karatnegara Kutai regional legislatures. While the secondary data obtained from the Parliament Secretariat and the Kutai regency General Elections Commission (KPU) Kutai Kartanegara.Unit analysis in this study is the Kutai District Council as an organization.The results of this study indicate that the performance of Parliament Kutai regency period 2009-2014 still low. It can be seen from the indicators of the tasks and functions of the Council, namely the function of representation, legislation, oversight and budget. The  low  performance  of Kutai Regency Parliament is influenced by not running the  Standard  Operating  Procedures  (SOP). To enhance or improve the performance of the board in the future, need to tighten up the system of selection / recruitment process of the council members through political parties, the establishment of an integrated information service center and body empowerment honor council.